94.2k views
3 votes
Let f(x)=6−2+2e−0.3x . What is f(−4) ?

User Drumkruk
by
5.7k points

2 Answers

4 votes

Answer: 1.3

Explanation:

User BFar
by
5.1k points
4 votes

Answer:

f(-4) = 10.636

Explanation:

In this problem we need to substitute and add together the remaining terms

f(x)=6−2+2e−0.3x

If we simplify

f(x) = (6−2) +2e−0.3x

f(x) = (4) +2e − 0.3x

We substitute the value for e (Euler's number)

e = 2.718

f(x) = (4) +2(2.718) − 0.3x

f(x) = (4) + 5.436 − 0.3x

f(x) = 9.436 -0.3*x

We just need to substitute for x = -4 , to get f(-4)

f(-4) = 9.436 -0.3*(-4)

f(-4) = 9.436 + 1.2

f(-4) = 10.636

User Nick Fortescue
by
5.6k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.